Modificação química de poli(ácido láctico) com anidrido maleico por processamento reativo - Rigolin, Talita Rocha (2014)
The chemical modification of PLA with maleic anhydride by reactive processing and the extent of reaction and degradation reactions, were studied. Routes of grafting reaction of maleic anhydride in PLA were evaluated. Dicumyl peroxide (DCP), as initiator, and maleic anhydride (MA) for modification of the PLA, were used. Acidity levels of the compositions were obtained by titration technique of the acid groups and observed an increase in acidity of the modified PLA s, with steep increase in the sample of PLA-g-MA, produced in the presence of DCP. During the PLA modification, with MA, was observed a reduction of 45% in Mn, measured by SEC. In order to analyse the reaction routes, PLA/PBAT blends were produced. Compatibilization of the blend was performed by two ways, one using in situ PLA/PBAT modification and the other using a pre-modified PLA (PLA-g-MA). A blend without MA (PLA/PBAT) was used as reference. In according with the observed mechanical behavior, a synergic effect is observed for PLA-g-MA/PBAT blend, despite low molecular weight of PLA matrix.